APARATUS FOR MEASURING MULTIPHASE CURRENT DIFFUSION BASED ON THE OPTOACOUSTIC EFFECT - T. R. Vasilyev; A. G. Kokuev (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. The purpose of the study is to provide an improved multiphase flow meter that meets the metrological and technical standards, the composition of which would exclude radioactive elements. Method. Instead of gamma radiation, the optoacoustic effect is proposed for use in the multiphase flow meter. The table shows the plan of the flow meter with a description of its assembly. The possibilities of using the optoacoustic effect for creating ultrasonic multiphase flow meter with high power emitters are also considered. Results. An analysis of modern multiphase flow meters, including the most popular, which utilise a nozzle within the design of the Venturi meter gamma densitometer. The advantages and disadvantages of the multiphase flow meters. Instead of the gamma ray method the use of the optical-acoustic effect is proposed. During laser irradiation of the medium, pressure wave were formed. Judging on the basis of pressure readings, the parameters of the medium can evaluated: optical density, medium density. Conclusion. The main requirement for a multi-phase flow meter is to achieve precision oil level readings during transport. Multiphase flow meters allow the principle implementation of the separate developed measure registering the quantity of produced gas-liquid mixture during the satellite fields development and wells belonging to different owners, i.e. offering a significant economic effect. It is evident that the multiphase flow meter will play a key role in optimising production control in oil and gas fields. It is necessary to continue research through series of experiments in order to verify the metrological characteristics and implementation possibilities of the technology.